2016
DOI: 10.3390/v8100264
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a Latent Indian Cassava Mosaic Virus from Cassava Which Recovered from Infection by a Non-Persistent Sri Lankan Cassava Mosaic Virus

Abstract: The major threat for cassava cultivation on the Indian subcontinent is cassava mosaic disease (CMD) caused by cassava mosaic geminiviruses which are bipartite begomoviruses with DNA A and DNA B components. Indian cassava mosaic virus (ICMV) and Sri Lankan cassava mosaic virus (SLCMV) cause CMD in India. Two isolates of SLCMV infected the cassava cultivar Sengutchi in the fields near Malappuram and Thiruvananthapuram cities of Kerala State, India. The Malappuram isolate was persistent when maintained in the Mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Also, some of the symptomless seedlings eventually succumbed to CMD at clonal evaluation. Scenarios of reemergence of latent Cassava mosaic virus have been observed previously from plants coinfected by two isolates, interacting in an antagonistic manner (Karthikeyan et al, 2016). One possible explanation would be that some seedlings had latent infection and eventually expressed CMD symptoms at clonal evaluation.…”
Section: Estimates Of Phenotypic and Genetic Correlations Among Traitsmentioning
confidence: 86%
“…Also, some of the symptomless seedlings eventually succumbed to CMD at clonal evaluation. Scenarios of reemergence of latent Cassava mosaic virus have been observed previously from plants coinfected by two isolates, interacting in an antagonistic manner (Karthikeyan et al, 2016). One possible explanation would be that some seedlings had latent infection and eventually expressed CMD symptoms at clonal evaluation.…”
Section: Estimates Of Phenotypic and Genetic Correlations Among Traitsmentioning
confidence: 86%
“…In Africa, e.g., Bemisia tabaci (Gennadius) transmits the viruses causing cassava brown streak disease (CBSD) and cassava mosaic disease (CMD), the latter also transmitted by this species in Southern Asia. Both CBSD and CMD annually cause losses of millions of dollars of cassava crops in both Africa and Indian subcontinent (Legg and Fauquet 2004, Ghosh et al 2015, Karthikeyan et al 2016).…”
mentioning
confidence: 99%
“…This agreed with the earlier reports of surveys performed using PCR and PCR-RFLP [11,13] and reinforced the view that SLCMV is more widespread than ICMV in India. Interestingly, a study has recently shown evidence of a possible suppression of ICMV accumulation by SLCMV, in case of joint infection of naturally infected cassava plants collected from the state adjoining Tamil Nadu, Kerala; the ICMV emerging only after ''recovery'' of the plant from SLCMV infection [32]. Our present observation of low incidence of joint infection with both ICMV and SLCMV and previous reports [11,13] indicated that ICMV can co-exist with SLCMV in many plants, indicating the existence of possibly more interacting relationships between the two viruses, other than that reported [32].…”
Section: Discussionmentioning
confidence: 99%